2018
DOI: 10.1371/journal.pone.0200950
|View full text |Cite
|
Sign up to set email alerts
|

Selective effects of Δ9-tetrahydrocannabinol on medium spiny neurons in the striatum

Abstract: Derivatives from the Cannabis plant are the most commonly abused illegal substances in the world. The main psychoactive component found in the plant, Δ-9-tetrahydrocannabinol (THC), exerts its effects through the endocannabinoid system. Manipulations of this system affect some types of learning that seem to be dependent on dorsal striatum synaptic plasticity. Dendritic spines exhibit important synaptic functional attributes and a potential for plasticity, which is thought to mediate long-lasting changes in beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 87 publications
1
3
0
Order By: Relevance
“…This is interesting in the general context of the involvement of the endocannabinoid systems in habit formation (60–62). We and others have shown that a regime of THC exposure in adult animals accelerated habit formation (62, 63) and, we also found that the THC treatment increased dendritic spine density in the distal part of the dendrites of medium spiny neurons in the posterior dorsomedial striatum (64) suggesting a potential mechanism of these alterations in the balance between goal-directed behaviour and habits. However, when the treatment occurred during adolescence, we observed no such behavioural effects.…”
Section: Discussionsupporting
confidence: 71%
“…This is interesting in the general context of the involvement of the endocannabinoid systems in habit formation (60–62). We and others have shown that a regime of THC exposure in adult animals accelerated habit formation (62, 63) and, we also found that the THC treatment increased dendritic spine density in the distal part of the dendrites of medium spiny neurons in the posterior dorsomedial striatum (64) suggesting a potential mechanism of these alterations in the balance between goal-directed behaviour and habits. However, when the treatment occurred during adolescence, we observed no such behavioural effects.…”
Section: Discussionsupporting
confidence: 71%
“…The persistent licking during the inter-food interval seen in the animals treated with THC may reflect some features of habit-like behaviours. In this regard, cannabinoids influence the transition from volitional behaviour to habit formation, and chronic exposure to them induces structural plasticity in the dorsal striatum, a region closely involved in this kind of behaviour (Fernandez-Cabrera et al 2018;Goodman and Packard 2015;Lovinger et al 2010). Recent research has demonstrated that rats subjected to the SID model exhibited greater habitual-like behaviour (Merchán et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…This observation fits the effects of AM251 treatment on DMS found in the present research, and makes us consider DMS as the crucial structure that may provide information about the role of CB 1 in the selection between navigational strategies. In fact, the multi-pronged observations that the manipulations on CB 1 activity modified DMS spine density [82], brought about changes in navigational behaviors (present findings, [41]), modulated c-Fos activation in DMS (present findings), are related to the presence of presynaptic CB 1 receptors (which is known to inhibit the neurotransmitter release) in both cortical glutamatergic afferents on and GABAergic terminals in MSN and in aspiny interneurons of dorsal striatum [83,84]. Furthermore, the present data indicate that to select more frequently the navigational strategy related to cognitive map it is required the full functionality of DMS neurons.…”
Section: Discussionmentioning
confidence: 99%